Luminescent composites by in-suit encapsulating dye in IRMOF-3 for ratiometric temperature sensing and tunable white light emission. (February 2022) - He, Caicai; Yu, Haihuan; Sun, Jing; Zhou, Cheng; Li, Xiao; Su, Zhong-Min; Liu, Fangbin; Khakhinov, Vyacheslav
Abstract: Metal-organic frameworks (MOFs) as a promising scaffold for functional guests, are known for the adjustable structures and various porosity, which can improve the luminescence performance by encapsulating fluorophores. Herein, the organic fluorescent dyes of rhodamine B (RhB) and fluorescein (FL) are immobilized in luminescent IRMOF-3, named as Dye@IRMOF-3, by a simple in-suit encapsulation reaction. Dye@IRMOF-3 are characterized by X-ray diffraction (XRD), gas adsorption analysis, thermogravimetric (TG), Fourier transform infrared (FTIR) and luminescent experiments. Dye@IRMOF-3 composites overcome the intrinsic problem of dye quenching caused by aggregation in solids, and show the fluorescence of both IRMOF-3 and dye molecules. In luminescence temperature sensing experiments, the relative sensitivity range of RhB@IRMOF-3 and FL@IRMOF-3 are from 0.60 to 0.87%°C −1 (temperature range of 20–70 °C) and 0.47–0.66%°C −1 (temperature range of 20–80 °C), respectively, making them promising colorimetric thermometer for field temperature measurements. Meantime, the emission spectrum of RhB/FL@IRMOF-3 can cover the whole visible light, whose CIE coordinates (0.330, 0.342) are quite close to those of the pure white light (0.333, 0.333), showing potential applications in the field of white light emission. This work provides a promising method for the synthesis of Dye@MOF luminescent materials and provides a new way to develop temperature-sensitive and white-emitting MOF materials by encapsulating different dye molecules. Highlights: Three Dye@IRMOF-3 composites were constructed by encapsulating dye molecules. The Dye@IRMOF-3 composite showed emission of both dye and IRMOF-3. Dye@IRMOF-3 composite materials have potential applications in temperature measurement. RhB/FL@IRMOF-3 composites can be used for white light emission.